Global technologies, local practices. Issue 3 (3rd July 2019) - Gallagher, Michael; Knox, Jeremy
ABSTRACT: This special issue of Learning, Media and Technology contributes to a growing need, not only for critical accounts of digital education that resist the global, but also for a more diverse representation of the multiplicitous practices of teaching and learning with technology across the globe. It builds on important work that has examined open education initiatives in the Global South [Arinto, P. B., C. Hodgkinson-Williams, and H. Trotter. 2017. "OER and OEP in the Global South: Implications and Recommendations for Social Inclusion." Adoption and Impact of OER in the Global South, 577–592] and highlighted 'missing voices' in educational technology development [Davis, R. 2015. The Missing Voices in EdTech: Bringing Diversity into EdTech . Thousand Oaks, CA: Corwin Press]. It is through such critical enquiry that research can continue to cut through the discursive regimes of simplistic disruption and enhancement from a pervasive education technology industry. This means aligning research in this area, less with grand narratives that portray digital education as an external and universal force capable of radical transformation, and more with accounts that acknowledge an already-present political economy of educational technology, in which specific devices and applications succumb to everyday practices of negotiation, consumption, and resistance, particular to the contexts in which they manifest.